2006
DOI: 10.1002/da.20148
|View full text |Cite
|
Sign up to set email alerts
|

OCD symptoms in a sample of Turkish patients: a phenomenological picture

Abstract: This study aimed to investigate the clinical features of obsessive-compulsive disorder (OCD) and the possible association between obsessive-compulsive symptoms and culture-related characteristics in a sample of Turkish patients with OCD. We studied 141 patients with OCD (according to DSM-IV criteria) consecutively admitted to our outpatient clinic during the period from February 1998 to December 2003. We used the Turkish version of the Structured Clinical Interview for DSM-IV (SCID) to interview all patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 27 publications
3
29
1
9
Order By: Relevance
“…46 According to some authors, more women present co-occurring major depressive disorder. 6,23,33 On the other hand, several studies found no gender differences regarding major depression comorbidity, which is the most common Axis I disorder in both genders. 21,22,24,25,37,47 In an Italian study, 19 men presented more social phobia, tic disorders, and hypomania episodes.…”
Section: Phenotypical Studiesmentioning
confidence: 98%
See 3 more Smart Citations
“…46 According to some authors, more women present co-occurring major depressive disorder. 6,23,33 On the other hand, several studies found no gender differences regarding major depression comorbidity, which is the most common Axis I disorder in both genders. 21,22,24,25,37,47 In an Italian study, 19 men presented more social phobia, tic disorders, and hypomania episodes.…”
Section: Phenotypical Studiesmentioning
confidence: 98%
“…Torresan et al 25 described earlier age of symptom interference among Brazilian men, who were also more likely than women to be single, which is consistent with findings from other countries. 18,23,34 Several other authors have also described that women with OCD are more frequently married than men. 14,22-24 Matsunaga et al, 34 evaluating 94 Japanese patients, found higher social interference of OCS among men, whereas women more frequently involved family members in their rituals.…”
Section: Phenotypical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Çocukluk çağında erkeklerde daha fazla görülürken, erişkin dönemde kadın erkek oranının yaklaşık olarak aynı olduğu ya da kadınlarda daha fazla görüldüğü bildirilmiştir 7,8 . Yazında kadınlarda en sık eşlik eden psikiyatrik eştanılar majör depresyon, yeme bozuklukları, dürtü kontrol bozuklukları iken, erkeklerde sosyal fobi, tik bozuklukları, madde kullanım bozukluklarıydı 9,11,[13][14][15][16][17]19 . Yaptığımız araştırmada ise cinsiyetler arasında psikiyatrik eştanı açısından istatistiksel olarak anlamlı bir farklılık bulunamamıştır.…”
Section: İlk Olarak Esquirol Tarafından Tanımlananunclassified